Business closure and financial loss: Who foots the bill? Evidence from German small business closures - Georg Metzger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper explores how different reasons for business closure impact the probability that financial loss will be suffered by creditors. Using German small business data, the study finds that business closure due to financial problems is strongly correlated with a likelihood of financial loss. By contrast, closures that take place based on expectations about a business' future development or because the owner takes a different earning opportunity are less likely to entail losses for creditors. The findings suggest that creditors are better off when entrepreneurs have a clear picture of their own abilities and shortcomings, and don't suffer from all-too-frequent over-optimism. Consequently, creditors stand to gain from helping clients to assess financial prospects.
Keywords: G33; L26; M13; 330; Bankruptcy; business closure; financial loss; Liquidation; Klein- und Mittelunternehmen; Konkurs; Zahlungsunfähigkeit; Kreditrisiko; Gläubiger; Deutschland